Practical skills and clinical management of alcoholism and drug addiction - Obembe, Samuel B. (Elsevier insights., 2012)
This insightful book is a synoptic presentation of Causes and Treatment of Alcoholism and Drug Addiction. It gives an insight into Alcoholism and Drug Addiction genetic and/or acquired etiologies through researched studies that draw the conclusion that Addiction is a disease/ medical condition. It features the treatment from detox followed by psychotherapy with evidence based practices and supported by Aftercare programs to maintain sobriety and recovery.